Cooperative breeding in Neolamprologus bifasciatus, a cichlid fish inhabiting the deep reefs of Lake Tanganyika. Issue 4 (10th April 2022) - Satoh, Shun; Saeki, Taiga; Kohda, Masanori; Awata, Satoshi
Abstract: Cooperative breeding, a social system in which offspring receive care from other group members as well as their parents, occurs in insects, fish, birds and mammals. In this study, we report a new example of cooperative breeding in the cichlid fish ( Neolamprologus bifasciatus ). This species, endemic to Lake Tanganyika, Africa, inhabits rocky areas at depths below 30 m. Observations of eight nests using underwater video cameras showed that one to six subordinates were present in the nests of breeding pairs. The subordinates shared shelters with juveniles and breeders and engaged in brood/territorial defence and nest maintenance (removing sand from the nest), albeit at a lower frequency than female breeders. The frequency of sand digging by subordinates and female breeders decreased as the number of subordinates in the group increased, suggesting that subordinates reduce the costs of nest maintenance for breeders. The male breeders seldom showed territorial defence and nest maintenance. Subordinates exhibited submissive behaviours towards dominant breeders and larger subordinates within their breeding group, indicating a dominance hierarchy among group members. Gonad examination revealed that the subordinates of both sexes were sexually immature, suggesting that they may not participate in reproduction. An aquarium experiment showed that juveniles become subordinates in their natal nest and participate in territory defence. We conclude that N.   bifasciatus is a cooperative breeder, with social systems and subordinate roles similar to those observed in other cooperatively breeding cichlids.